Geotecnologias aplicadas a gestao do patrimonio cultural na cidade da Lapa (PR): construção do Atlas Digital do Patrimônio Arquitetônico - Burda, Naomi Anaue (2009)
This research searched to contribute for the management of the cultural patrimony architectural of city of the Lapa, through the elaboration of Digital Atlas of the Historic Architectural patrimony of the Historical Center using geotechnologies. There was the use of the geotechnologies, as the Digital Cartography, Remote Sensoriament, Global Positioning system and System of Geographic Information, that had been the base for the elaboration of Digital Atlas. The justification is in the necessity of instruments for aid of the management of the patrimony, as the Digital Atlas, to be implanted and to be used in the public administration and by the society. The geotechnologies are important for the municipal management, therefore it is increasing the demand for processes of integration of informations, and the georreferencing of the same ones. The line theoretician-metodologic adopted was the chain of critical geography, therefore it establishes a critical reading of the phenomena, trying to diminish the partner-economic and regional differences, understanding that they result of relations of power. Critical geography has a proposal pluralist and opened, dialoguing with diverse chains and its characteristics they are to consider the social boarding; the phenomena if materializing in the space; e the union between object and citizen, influenced to the social view of world of the investigator. The results of this research reveal a Historical Center with preserved constructions, but deficient as much the technical instruments, especially cartographic information, that can contribute for the activities of management of the cultural patrimony architectural. This space is subject to the rules of the capitalist exploration, but in compensation there is also an identification of the society while part integrant of this architectural patrimony, where the styles of the casarios are like a form of materialization of the social production of a time. Also the necessity of instruments as these Digital Atlas, to be implanted and to be used in the public administration, aiming at one better administration and use of the rchitectural patrimony in its knowledge form, spreading and fruition for the society in an ampler form.